From drag to brag: The role of government grants in enhancing built heritage protection efforts in New Zealand's provincial regions. (October 2021) - Aigwi, Itohan Esther; Filippova, Olga; Ingham, Jason; Phipps, Robyn
Abstract: The protection of heritage buildings is essential because they signpost the narration of a community's past into the future. Investment in the protection of heritage buildings through incentives in the form of government grants provides a lifeline for the future preservation of built heritage, which can boost an urban area's local economy. This study sought to evaluate the distribution of heritage buildings in New Zealand, examine the allocation of significant government funding sources for protecting the heritage buildings, and explore the implications of this allocation on future built heritage protection efforts in New Zealand's provincial regions. An analysis of existing relevant documents revealed that while the per capita distribution of heritage buildings was highest in New Zealand's provincial regions, major urban centres received the highest share of government funding. Findings from key informant interviews identified three major themes as implications of the current incentive allocation on built heritage protection efforts in New Zealand's provincial regions: (i) disproportionately low allocation of government grants to provincial regions; (ii) lack of sophistication among property investors in provincial regions; and (iii) "emergency solution" mindset of government funding regulators. These findings imply that though government heritage grant systems are the most extensive non-regulatory incentives for the protection of built heritage in New Zealand, the provincial regions currently struggling with so many underutilised and derelict historical buildings may not be able to keep up with their preservation efforts if they continue to receive a lesser proportion of the available grant. As a recommendation, the central government can assist by directing more discretionary grants to provincial regions to encourage future efforts towards protecting their heritage buildings. Highlights: Investment in the protection of heritage buildings through government grants provides a lifeline for the protection of built heritage. Although the per capita distribution of heritage buildings is highest in New Zealand's provincial regions, major urban centres often receive the highest share of government funding. It is recommended that the New Zealand government can assist by channelling more discretionary grants to provincial regions to encourage future efforts towards protecting their heritage buildings.